Assessing Community Resilience: An Application of the Expanded CART Survey Instrument With Affiliated Volunteer Responders. (February 2015) - Pfefferbaum, Rose L.; Pfefferbaum, Betty; Nitiéma, Pascal; Houston, J. Brian; Van Horn, Richard L.
This article describes an application of the Communities Advancing Resilience Toolkit Assessment Survey using a sample of affiliated volunteer responders. The Communities Advancing Resilience Toolkit Assessment Survey is a theory-based, evidence-informed instrument. Early applications of the survey identified four domains: Connection and Caring, Resources, Transformative Potential, and Disaster Management. The version of the instrument used in the current application added items related to Information and Communication, thus creating a fifth domain. The application confirmed the five-factor model and the instrument demonstrated good reliability. Affiliated volunteer responders served as key informants regarding community resilience because of their involvement in local disaster readiness and response. Home ownership and active membership in an affiliated volunteer responder group were associated with the total community resilience score and with multiple domain scores, suggesting the importance of community member investment and engagement for a community's resilience. Although the study sample involved affiliated volunteer responders, it is likely that engagement in other community organizations and activities may yield similar benefits for resilience.